Editorial: New Perspectives on Conceptual Growth through GT - Astrid Gynnild (Grounded Theory Review: An International Journal)
What does it mean to learn grounded theory? I mean, really learn it? The question emerged while re-reading and reflecting on the final versions of the six very different, and yet interrelated, articles in this June issue of the Grounded Theory Review.